Magnetic resonance cholangiography in patients with bile duct obstruction - Lincender, Lidija (Radiology and oncology (Ljubljana), 2000)
Background. The aim of this study was to assess the diagnostic value of magnetic resonance cholangiography (MRC). This is a new non-invasive imaging technique for the evaluation of bile duct obstruction. Patients and method. MRC was performed on patients with bile duct obstraction at 1.0 TU. Over a period of 26 months, 44 patients, 23 males and 21 females, mean age 51 years, were examined. The basis were T2-weighted sequences through liver to accentuate the fluid fill bile duct, and fast spin echo sequences. Usually, the thickness of the slices was 4 mm. Two spatial planes were performed, coronal and axial, with the breath held and released, and with maximum intensity projection (MIP) reconstruction. In our case, with Machine 1.0T, we comapred the results of ultrasound and CT with MRC in the patients with bile duct obstruction before surgical intervention or drainage procedure. Results. We examined 44 patients with jaundice by MRC and with the 100% accuracy identified the level of the obstruction. Clinical applications of MRC were evaluated on the basis of personal experience, and data literature. The main indication for MRC study was the evaluation of common bile duct obstruction without using contrast medium and biliary intervention. Conclusions. MR technique has been dictated by image performance and sequence availability. Our experience and results confirmed that MRI is more accurate than US and CT in patients with bile duct obstruction.
Keywords: Bile duct neoplasms; Cholangiocarcinoma; Cholangiography; Cholelithiasis; Cholestasis; Diagnosis; diagnostika; Liver neoplasms; Magnetic resonance imaging; Pancreatic neoplasms; slikanje z magnetno resonanco; zapora; žolčevod